Assessment of energy expenditure in individuals with post-poliomyelitis syndrome - Roberto Dias Batista Pereira; Tatiana Mesquita e Silva; Abrahão Augusto Juviniano Quadros; Marco Orsini; Beny Schmidt; Helga Cristina Almeida Silva; Acary Souza Bulle Oliveira (Arquivos de Neuro-Psiquiatria)
ABSTRACT The objective of this study was to identify energy expenditure, retrospectively, in individuals with post-poliomyelitis syndrome (PPS) in the Brazilian population. Methods The Baecke questionnaire for the evaluation of habitual physical activity (HPA), assessment of quality of life (WHOQOL-Bref), and the Fatigue Severity Scale were administered to patients with PPS, poliomyelitis sequelae (PS) and to a control group (CG). Participated in the study 116 individuals (PPS=52,PS= 28,CG=36). Results Patients with PPS tended to increase their HPA from 10 to 20 years of age, compared with those in the PS group and the CG. In the period from 21 to 30 years of age, there was significant increase in the PPS group’s occupational physical activity compared to the PS group, and the occupational physical activity (21-30 years of age) correlated with the onset of symptoms of PPS. Conclusion Patients with PPS had a higher energy expenditure during life, especially in occupational physical activity at ages 21-30 years, suggesting this decade is critical for the development of PPS.